Factors Influencing Adolescent Behavior in HIV/AIDS Prevention - Marni, Marni; Firdaus, Insanul; Yudhianto, Kresna Agung; wahyuningsih, Wahyuningsih; Hanung, Allania; Ernawati, Wahyu (Global Health Science Group, 2024)
The Indonesian Ministry of Health highlights that HIV cases are starting to be dominated by young people. The latest data shows that around 51 percent of new HIV cases detected are in teenagers (Rondonuwu, 2022). HIV/AIDS prevention is very necessary for teenagers, considering that the incidence rate is quite high. In this study, research related to factors influencing HIV/AIDS prevention behavior in adolescents will be presented in terms of adolescent knowledge, family and adolescent social support. The aim of this research is to analyze research that has been published in journal form. The research method uses PRISMA, the author searches for journals, identifies, reviews and adjusts them to appropriate criteria so that 8 journals are selected for analysis. Research results: of the 8 journals analyzed, knowledge has a large influence on preventing HIV/AIDS in adolescents. Family and social peer support also has an influence on it, especially in the cultural norms and values that apply where teenagers live. Conclusion: Education for groups of teenagers is prioritized so that teenagers have a good peer social environment, thereby creating high self-awareness among teenagers to behave positively in preventing HIV/AIDS.